If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -5) = 2x + 90 Reorder the terms: 4(-5 + 3x) = 2x + 90 (-5 * 4 + 3x * 4) = 2x + 90 (-20 + 12x) = 2x + 90 Reorder the terms: -20 + 12x = 90 + 2x Solving -20 + 12x = 90 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -20 + 12x + -2x = 90 + 2x + -2x Combine like terms: 12x + -2x = 10x -20 + 10x = 90 + 2x + -2x Combine like terms: 2x + -2x = 0 -20 + 10x = 90 + 0 -20 + 10x = 90 Add '20' to each side of the equation. -20 + 20 + 10x = 90 + 20 Combine like terms: -20 + 20 = 0 0 + 10x = 90 + 20 10x = 90 + 20 Combine like terms: 90 + 20 = 110 10x = 110 Divide each side by '10'. x = 11 Simplifying x = 11
| 12x+54+12x+54= | | z^2-7=-18 | | N+(-4)=31 | | 7.5=(h+3)/2 | | K^2+9k-39=-k | | 7x-4(7x+6)=-192 | | t=7s-2 | | 81=1-5(x-8) | | 3x-6=-16 | | 0.25(20)+0.15x=0.10(20+x) | | 130x=48393 | | 3(m+3)-5=16 | | 1(x+2)-3(x-3)=5(2) | | 6xsquared+4x=0 | | 4v-5(8+6v)=-118 | | 10h=16 | | 8*x-3=40 | | 4c+9= | | 9x-84+85=5x+77 | | w^2+7w-20580=0 | | -2(6y-2)+4y=2(y+4) | | 0.20a-54.40=a | | 3z+3z=5z+2 | | 18=12x+3y | | 36b-3=o | | 128=144x-16x^2 | | -3(1-8a)=117 | | -8a-2a=6-5a-3a | | 18x^3-63x^2=9x | | 6-(-x)=-13 | | (4+2-8)*(4+5)*1876= | | -(2y-2)+4y=2(y+4) |